Методика конфігурування служб Windows 10 редакцій Home та Pro для персональних комп’ютерів з використанням технології віртуалізації - Рибачок, Н.А.; Заболотня, Т.М.; Люшенко, Л.А.; Сущук-Слюсаренко, В.І. (Управляющие системы и машины, 2018)
Запропоновано методику налаштування рівня запуску служб Windows 10 редакцій Home та Pro для персональних комп’ютерів з використанням технології віртуалізації, коли всі процедури налаштування служб виконуються на «еталонній» операційній системі, встановленій на віртуальній машині, а потім ці налаштування переносяться на «основну» систему. Застосування методики надає ряд переваг при виконанні робіт із супроводження операційної системи в промислових масштабах. Методика може бути розширена на інші пристрої, де встановлено Windows. Предложена методика настройки уровня запуска служб Windows 10 редакций Home и Pro для персональных компьютеров с использованием технологии виртуализации, когда все процедуры настройки служб выполняются на «эталонной» операционной системе, установленной на виртуальной машине, а затем эти настройки переносятся на «основную» систему. Применение методики дает ряд преимуществ при выполнении работ по сопровождению операционной системы в промышленных масштабах. В дальнейшем методика может быть расширена на другие устройства, где установлена Windows. The purpose of the given research is to develop a methodology of services configuring in Windows 10 Home and Pro editions using virtualization technology, which can be applied to desktops and laptops. Methods. For the Windows 10 services configuration it is recommended to use the “model” OS that is installed on the virtual machine. An iterative procedures for OS services configuring are need to be done at the “model” OS. As a result, a tweak that contains the value of the registry parameters that are responsible for the Windows services run level setting will be created. Then the created tweak is used for transferring the services settings to the “main” OS. Results. The presented methodology of services configuration in Windows 10 can be used for reducing of the OS boot time, the computer system’s performance improving, and unnecessary services disabling.